Narratologiese ondersoek en eksegese van die boodskap van die evangelies - Gräbe, I. (Hervormde teologiese studies, 1986)
Narratological investigation and exegesis of the message of the gospels This paper argues that the narrative structure of the gospels facilitates the communication of the Biblical message and that exegesis of this message therefore presupposes an assessment of the semantic implications revealed through an analysis of particular genre conventions utilized in the narration of Biblical material. The narrative structure of the gospels shows striking correspondences with basic narrative forms such as fairy tales, so that an analysis of the narrative material on the basic story level, rather than on the level of narrative presentation, seems appropriate. In fact, the correspondence between the levels of story and narrative (Genette 1980) ensures that the deep structure or story content is directly projected onto the surface structure of the narrative text, resulting in a clear communication of the Biblical message.